An Optimized Anti-adherence and Anti-biofilm Assay: Case Study of Zinc Oxide Nanoparticles versus MRSA Biofilm - Hefa Mangzira Kemung; Loh Teng-Hern Tan; Kooi Yeong Khaw; Yong Sze Ong; Chim Kei Chan; Darren Yi Sern Low; Siah Ying Tang; Bey-Hing Goh (Progress in Microbes and Molecular Biology)
Biofilms form protective layers over bacteria that are associated with a majority of the hospital infections contributing to antibiotic resistance development in susceptible strains. Nowadays, there is a pressing need for developing effective anti-biofilm agents to help address the growing problem of biofilm-producing bacteria associated with antibiotic resistance. In recent years, zinc oxide nanoparticles (ZnO-NPs) has emerged as a prospective candidate for new anti-biofilm agents. The present method paper described an optimized anti-adherence and anti-biofilm assay using ZnO-NPs. The antibiotic-resistant bacteria Methicillin-resistant Staphylococcus aureus (MRSA ATCC4330) and vancomycin were used as the growth control and positive control, respectively. The result showed concentration-dependent anti-adherence and antibiofilm activity. The ZnO-NPs effectively prevented attachment of bacterial cells onto walls of wells with 51.69 ± 2.55% at the highest concentration tested (65.4 µg/mL). ZnO-NPs was also able to break-up 50% pre-formed MRSA biofilm at the lowest concentration of 13.5 µg/mL. Interestingly, ZnO-NPs at lower concentrations demonstrated significantly stronger antibiofilm activity than that of the positive control vancomycin, demonstrating that ZnO-NPs is a promising anti-biofilm agent. This method could be used as a preliminary screening of transition metal oxide nanoparticles as potential anti-adherence and anti-biofilm agents followed by other specific anti-biofilm assays.